Dynamic simulation and control structures of feed conditioning system for CO2 capture - Othman, N.A. (2019)
Supersonic Gas Separation technology for CO2-NG separation is based on the phase change of the gas mixture component. Simulation technique is typically used to design the SGS separator geometry to optimize the separation efficiency. This approach is economically feasible if compared to experimental method, which requires the manufacturing of SGS technology for testing purpose. However, there are limited studies on the simulation and control design which are crucial to test the stability and dynamic responses of the feed conditioning plant for SGS technology. This paper investigates the optimal regulatory plant-wide control strategy for the feed conditioning plant subjected by various disturbances in temperature, pressure and feed CO2 composition. The result shows that overall plant energy and sustainability can be improved using the dynamic analysis of plant control structure system. Copyright Â© 2019, AIDIC Servizi S.r.l.